2010
DOI: 10.29333/ejgm/82890
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Household Structure on The Prevalence of Food Insecurity

Abstract: Aim: Food insecurity is common in both developed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 7 publications
2
8
1
1
Order By: Relevance
“…In the current study, we found that more than half of subjects were living in marginal and moderate food insecure households (71.3%), which is in line with recent evidence that Middle-East and North Africa (Kamrava et al, 2012) is one of the most food insecure regions in the world. The figure is comparable with reports from the rest of Iran, which vary from 49% in North-East (Behzadifar et al, 2016) and 59% in the North-West (Sharafkhani et al, 2010) to 86% in the South (Kaldeh et al, 2010). However, as expected, the incidence of FI is much higher than the developed world; for example, FI is 10% in Canada (Tarasuk et al, 2014) and 14.3% in the US (Coleman-Jensen et al, 2014).…”
Section: Resultssupporting
confidence: 84%
“…In the current study, we found that more than half of subjects were living in marginal and moderate food insecure households (71.3%), which is in line with recent evidence that Middle-East and North Africa (Kamrava et al, 2012) is one of the most food insecure regions in the world. The figure is comparable with reports from the rest of Iran, which vary from 49% in North-East (Behzadifar et al, 2016) and 59% in the North-West (Sharafkhani et al, 2010) to 86% in the South (Kaldeh et al, 2010). However, as expected, the incidence of FI is much higher than the developed world; for example, FI is 10% in Canada (Tarasuk et al, 2014) and 14.3% in the US (Coleman-Jensen et al, 2014).…”
Section: Resultssupporting
confidence: 84%
“…First, our meta-analysis included only information from 2 national recallbased and several local perceptionbased studies. There were 2 studies in the north-west of the country (13,14) that were excluded due to lack of data on the different levels of food insecurity, as explained earlier. The perceptionbased studies included were conducted mainly in the central part of the Islamic Republic of Iran.…”
Section: Discussionmentioning
confidence: 99%
“…The family member is mostly more than 4 (67.6% in BED adolescents and 70.3% in non-BED adolescents). Sharafkhani et al (2010) revealed that food insecure household conditions were not related to the number of children. However, the presence of toddlers and elderly among family members can increase the risk of food insecurity.…”
Section: Respondent Characteristicsmentioning
confidence: 94%